Morphological, Behavioral, and Molecular Characterization of Avian Schistosomes (Digenea: Schistosomatidae) in the Native Snail Chilina dombeyana (Chilinidae) from Southern Chile - Pablo Oyarzún-Ruiz; Richard Thomas; Adriana Santodomingo; Gonzalo Collado; Pamela Muñoz; Lucila Moreno (Pathogens, 2022)
Avian schistosomes are blood flukes parasitizing aquatic birds and snails, which are responsible for a zoonotic disease known as cercarial dermatitis, a hypersensitive reaction associated to the cutaneous penetration of furcocercariae. Despite its worldwide distribution, its knowledge is fragmentary in the Neotropics, with most of data coming from Argentina and Brazil. In Chile, there are only two mentions of these parasites from birds, and one human outbreak was associated to the genus “Trichobilharzia”. However, the identity of such parasites is pending. The aim of this study was to identify the furcocercariae of avian schistosomes from Southern Chile using an integrative approach. Thus, a total of 2283 freshwater snails from different families were collected from three different regions. All snails were stimulated for the shedding of furcocercariae, but only Chilina dombeyana (Chilinidae) from the Biobío region was found to be parasitized. The morphology and phylogenetic analyses of 28S and COI genes stated two lineages, different from Trichobilharzia, shared with Argentina. This study provides new information on Neotropical schistosomes, highlighting the need for major research on these neglected trematodes, which are considered to be emerging/re-emerging parasites in other parts of the globe as consequence of anthropogenic disturbances and climatic change. Highlights: 1. Two different lineages (Lineage I and II) were described and molecularly characterized (28S and COI genes); 2. Cercaria chilinae I y II are proposed as a synonymous of Lineage II. Thus, a total of four different lineages of avian schistosomes are related to Chilina spp.; 3. Chilina spp. represents an important intermediate host for avian schistosomes in South America, constituting a reservoir de schistosomes with zoonotic potential; 4. Coinfection between the two different lineages was found, a finding previously not reported for avian schistosomes; 5. Expansion in the geographic distribution of Nasusbilharzia melancorhypha from its original record in Argentina, with Chilina dombeyana as an additional intermediate host.